2022
DOI: 10.1111/1750-3841.16353
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related alterations in the nutritional quality of Arctic grayling (Thymallus arcticus)

Abstract: The biochemical composition of the muscle in Arctic graylings at three age stages was evaluated and compared. For conventional biochemical composition, there was no significant difference in the crude protein content among the three age stages, but the crude fat content in the 1 year old was significantly lower than that of the others (P < 0.05). For amino acids composition, there was no significant difference in the content of essential amino acids and delicious amino acids among the three age stages, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…And another study showed the correlation between morphological traits and body weight of 1 + ~3 + ages Thymallus arcticus , and showed morphological traits correlated with body weight are dissimilar in different ages. The number of traits decreased with the increased of ages [ 27 ]. Similarly, Liu studied the association between body weight and morphological traits of Larimichthys crocea in 13 and 20 months [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…And another study showed the correlation between morphological traits and body weight of 1 + ~3 + ages Thymallus arcticus , and showed morphological traits correlated with body weight are dissimilar in different ages. The number of traits decreased with the increased of ages [ 27 ]. Similarly, Liu studied the association between body weight and morphological traits of Larimichthys crocea in 13 and 20 months [ 28 ].…”
Section: Discussionmentioning
confidence: 99%